Shortening the adaptation of Nellore cattle to high-concentrate diets using only virginiamycin as sole feed additive negatively impacts ruminal fermentation and nutrient utilization - Squizatti, Mariana M.; Rigueiro, André L. N.; Silvestre, Antonio M.; Soares, Carlos H. G.; Assumpção, Alice H. P. M.; Dias, Evandro F. F.; Felizari, Luana D.; Silva, Leandro A. F.; Souza, Katia L. R.; Carvalho, Victor M.; Demartini, Breno L.; Souza, Johnny M.; et al. (Frontiers in Veterinary Science, 2023)
Feedlot cattle are usually adapted to high-concentrate diets containing sodium monensin (MON) in more than 14 days. However, considering that the dry matter intake DMI is usually lower during adaptation when compared to the finishing period, the use of MON during adaptation may decrease even further the DMI, and virginiamycin (VM) may be an alternative. This study was designed to investigate the effects of shortening the adaptation length from 14 to nine or six days on ruminal metabolism, feeding behavior, and nutrient digestibility of Nellore cattle fed high-concentrate diets containing only VM as the sole feed additive. The experimental design was a 5 x 5 Latin square, where each period lasted 21 days. Five 17 mo-old Nellore yearling bulls were used (415±22 kg of body weight), which were assigned to five treatments: 1) MON (30 mg/kg) and adaptation for 14 days; 2) MON (30 mg/kg) + VM (25 mg/kg) and adaptation for 14 days; 3) VM (25 mg/kg) and adaptation for 14 days; 4) VM (25 mg/kg) and adaptation for 9 days, and 5) VM (25 mg/kg) and adaptation for 6 days. A quadratic effect for adaptation length when only VM was fed was observed for mean pH (P= 0.03), duration of pH below 5.2 (P= 0.01) and 6.2 (P= 0.01), where cattle consuming VM adapted for 9 days had higher mean pH and shorter period of pH below 5.2 and 6.2. Cattle that consumed only MON had a lower concentration of butyrate (P= 0.02) and a higher concentration of propionate (P= 0.04) when compared to those consuming VM and adapted for 14 days. As the adaptation length decreased for animals consuming only VM, the rumen degradability of dry matter (P< 0.01), neutral detergent fiber (P< 0.01), and starch (P< 0.01) decreased; however, protozoa numbers of Entodinium and total protozoa increased. It is not recommended to shorten the adaptation length of these animals to either 6 or 9 days without negatively impacting nutrient disappearance and ruminal fermentation patterns.